2004
DOI: 10.1017/s002193200400656x
|View full text |Cite
|
Sign up to set email alerts
|

Isonymy and the Structure of the Provençal-Italian Ethnic Minority

Abstract: Surnames were obtained for the second half of the 20th century from civil and religious marriage registers on fifteen Provençal-Italian and five Italian villages of Cuneo Province, Italy. To insert in the analysis an outward comparison, surnames from two Italian villages of Turin Province, one parish of Turin, one village of Alessandria Province and one village of Asti Province were also collected. Ethnicity does not seem to be the main factor affecting the present genetic structure of the Provençal-Italians. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…According to Koervelyessy et al (1992) and Manni et al (2004), the religious factor is important as revealed by RP as an indicator of population subdivision. But ethnicity was declared a secondary factor in other studies in comparison to geography (Vienna & Biondi, 2001;Biondi et al, 2005;Tagarelli et al, 2007). The combined effect of political and geographic barriers was studied by Eizaguirre (1994) at the northern Portugal-Spain border defined by the Miño River.…”
Section: Repeated-pairs Of Surnamesmentioning
confidence: 95%
See 1 more Smart Citation
“…According to Koervelyessy et al (1992) and Manni et al (2004), the religious factor is important as revealed by RP as an indicator of population subdivision. But ethnicity was declared a secondary factor in other studies in comparison to geography (Vienna & Biondi, 2001;Biondi et al, 2005;Tagarelli et al, 2007). The combined effect of political and geographic barriers was studied by Eizaguirre (1994) at the northern Portugal-Spain border defined by the Miño River.…”
Section: Repeated-pairs Of Surnamesmentioning
confidence: 95%
“…The genetic structure of a population depends on demographic, geographic and socio-cultural factors. Language, ethnicity, religious affiliation and occupation are variables that have been analysed (Smith et al, 1984;Koertvelyessy et al, 1988;Vienna & Biondi, 2001;Manni et al, 2004;Biondi et al, 2005;Tagarelli et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Italy has been a land of diverse population migrations, each of which left a mark on the cultural landscape (Salvi, ). Among the numerous linguistic minorities, the Provençal of the Italian Alps, the Croatian communities in Molise and the Arbëreshe, an Albanian‐speaking ethnic minority, have been broadly analyzed from both a biodemographic (Biondi et al, ; Fiorini et al, ; Tagarelli et al, ) and a genetic point of view (Babalini et al, ; Boattini et al, ; Capocasa et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The genetic structure of a population is largely determined by its degree of endogamy, with isolation by distance being one of the most widely studied factors (Lasker, 1985;Jorde & Morgan, 1987). The effect of geographic distance from neighbouring populations on genetic kinship is intensified by the existence of geographical environmental boundaries such as mountains or rivers, as well as cultural barriers including linguistic, ethnic or religious differences (Smith et al, 1984;Koertvelyessy et al, 1988;Zei et al, 1993;Vienna & Biondi, 2001;Tasso et al, 2005;Biondi et al, 2005;Tagarelli et al, 2007).…”
Section: Introductionmentioning
confidence: 99%